Network Meta‐Analysis on the Mechanisms Underlying Alcohol Augmentation of COVID‐19 Pathologies. (20th March 2021) - Huang, Wenfei; Zhou, Heping; Hodgkinson, Colin; Montero, Angelo; Goldman, David; Chang, Sulie L.
Abstract : Background: The coronavirus disease 2019 (COVID‐19) pandemic is a worldwide crisis caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Many COVID‐19 patients present with fever in the early phase, with some progressing to a hyperinflammatory phase. Ethanol (EtOH) exposure may lead to systemic inflammation. Network meta‐analysis was conducted to examine possible relationships between EtOH consumption and COVID‐19 pathologies. Methods: Molecules affected by EtOH exposure were identified by analysis with QIAGEN Knowledge Base. Molecules affected by COVID‐19 were identified from studies in MEDLINE, bioRxiv, and medRxiv reporting gene expression profiles in COVID‐19 patients, QIAGEN Coronavirus Network Explorer, and analysis of the RNA‐sequencing data of autopsied lungs of COVID‐19 patients retrieved from the GEO database. Network meta‐analysis was then conducted on these molecules using QIAGEN Ingenuity Pathway Analysis (IPA). Results: Twenty‐eight studies reporting significant gene expression changes in COVID‐19 patients were identified. One RNA‐sequencing dataset on autopsied lungs of COVID‐19 patients was retrieved from GEO. Our network meta‐analysis suggests that EtOH exposure may augment the effects of SARS‐CoV‐2 infection on hepatic fibrosis signaling pathway, cellular metabolism and homeostasis, inflammation, and neuroinflammation. EtOH may also enhance the activity of key mediators including cytokines, such as IL‐1β, IL‐6, and TNF, and transcription factors, such as JUN and STAT, while inhibiting the activity of anti‐inflammatory mediators including glucocorticoid receptor. Furthermore, IL‐1β, IL‐6, TNF, JUN, and STAT were mapped to 10 pathways predicted to associate with SARS‐CoV‐2 proteins, including HMGB1, IL‐1, and IL‐6 signaling pathways. Conclusions: Our meta‐analyses demonstrate that EtOH exposure may augment SARS‐CoV‐2–induced inflammation by altering the activity of key inflammatory mediators. Our findings suggest that it is important for clinicians to caution patients about the risk of alcohol consumption, which has increased during the COVID‐19 pandemic. The findings also call for further investigation into how alcohol exposure affects viral infections. Abstract : Our network meta‐analysis reveals alcohol consumption may augment COVID‐19 pathologies. Ethanol enhances the effects of SARS‐CoV‐2 infection on hepatic fibrosis signaling pathway, cellular metabolism and homeostasis, inflammation, and neuroinflammation. It also increases the activity of cytokines including IL1β, IL6, and TNF, and transcription factors including JUN and STAT, while inhibiting the activity of anti‐inflammatory mediators including glucocorticoid receptor. IL1β, IL6, TNF, JUN, and STAT are key components of pathways affected by COVID‐19, including HMGB1, IL1, and IL6 signaling pathways.